Francophone African narratives and the Anglo-American book market ferment on the fringes - Steemers, Vivan 1958- (After the empire: the Francophone world and postcolonial France, 2021)
"Ferment on the Fringes charts the trajectories of Francophone African narratives that reached the Anglo-American market, by analyzing the various institutional agents and agencies involved in the value-making process that accrues visibility to translated texts that eventually reach the Anglo-American book market"--